Make : electronics - Platt, Charles (Maker Community, 2021)
Make: Electronics, 3rd Edition explores the properties and applications of discrete components that are the fundamental building blocks of circuit design. Understanding resistors, capacitors, transistors, inductors, diodes, and integrated circuit chips is essential even when using microcontrollers. Make: Electronics teaches the fundamentals and also provides advice on the tools and supplies that are necessary. Single bus breadboards are now used throughout, diagrams rather than photographs show circuit placement, internal circuit illustrations have been redrawn for clarity, and an expanded focus on Arduino as the most popular microcontroller distinguish this third edition. Unchanged are the dry humor and clear explanations that have made this a best selling book for over 10 years and counting. Get ready to burn things out and mess things up, because that's how you learn!